Media Sosial dan Karakter Religius Siswa: Studi Pengaruh Instagram pada Siswa MAN Purworejo - Murtadho, Khamid; Fatkhurrohman, Fatkhurrohman; Firdaus, Firdaus (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to examine how Instagram use influences the religious character of students at Madrasah Aliyah Negeri (MAN) Purworejo. The research employed a quantitative approach with an explanatory design. Data were obtained through an online questionnaire distributed via Google Forms to official WhatsApp groups for grades X, XI, and XII. From an initial total of 169 participants, 164 valid responses were retained after removing outliers. The sampling technique applied was non-probability sampling using an incidental sampling strategy. Data analysis was carried out using simple linear regression with SPSS Statistics version 30. The findings reveal that Instagram usage has a positive and statistically significant effect on students’ religious character (β = 0.641; p < 0.001; R² = 0.299). This indicates that the more frequently students engage with religious content on Instagram, the stronger their religious character tends to be. These results reinforce Cultivation Theory, which posits that social media can shape moral and spiritual values through repeated exposure to specific messages.